The journey of the one and only Declaration of Independence - St. George, Judith, 1931- (Philomel Books, 2005)
In 1776 Thomas Jefferson put his quill to paper and the Declaration of Independence sprang to life. Follow the Declaration's journey over the next two centuries, surviving eight wars and travelling through five states on horseback, boat, railcar, and tank to its current home in the National Archives.